(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2026)
The paper explores the benefits of applying information and communication technologies in subject instruction, such as fostering students’ knowledge and competencies, increasing instructional efficiency, personalizing training activities, and strengthening student motivation.